Konstruksi Sosial Ibn Al-Farabi dalam Masyarakat di Permukiman Magersari Keraton Kasepuhan dan Kanoman Cirebon - Kintan Ayu Sevila; Ina Helena Agustina (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. The increase in population which is in line with the increasing need for housing has made the Magersari of Kasepuhan and Kanoman Palaces no longer only intended for courtiers. As a heritage area that is a witness to the history and culture of the Palace from time to time, the Magersari residential social condition in Kasepuhan and Kanoman palaces must have changed along with the entry of immigrants who were neither courtiers nor relatives of the palace. Given the changes that happen to social conditions will affect the meaning formed in social space, the social construction of the Magersari settlements, Keraton Kasepuhan, and Kanoman is a highlight to study. Usage of Ibn Al-Farabi's theory is based on Magersari's background as a heritage area of ​​the Cirebon Sultanate constitutes an Islamic kingdom and also Al-Farabi is an Islamic philosopher and thinker. After a series of observations and in-depth interviews, the author tries to interpret the phenomena caught by using the social construction formulation of Ibn Al-Farabi's theory. Based on empirical findings, it was discovered that the Magersari settlers have positive, optimistic, and open thoughts. Fellow settlers always help each other and have a sense of kinship but still provide boundaries so that they are not too excessive. The settler community still adheres to Islamic values ​​and culture. However, these values ​​began to fade among young people in line with their reluctance to participate in routine agendas in the Magersari settlement, as well as traditional and cultural events held by the Keraton. Abstrak. Peningkatan populalsi yang sejalan dengan peningkatan kebutuhan akan tempat tinggal membuat Magersari Keraton Kasepuhan dan Kanoman tak lagi hanya diperuntukan bagi para abdi dalem. Sebagai kawasan heritage yang merupakan saksi dari sejarah dan kebudayaan Keraton dari masa ke masa, keadaan sosial permukiman Magersari Keraton Kasepuhan dan Kanoman pasti mengalami perubahan seiring dengan masuknya para pendatang yang bukan merupakan abdi dalem maupun kerabat Keraton. Mengingat perubahan yang terjadi pada keadaan sosial akan mempengaruhi pemaknaan yang terbentuk terhadap ruang sosial, maka konstruksi sosial dari permukiman Magersari Keraton Kasepuhan dan Kanoman menjadi hal yang penting untuk diteliti. Penggunaan teori dari Ibn Al-Farabi didasari oleh latar belakang Magersari sebagai kawasan heritage dari Kesultanan Cirebon yang merupakan kerajaan Islam dan Al-Farabi yang merupakan filsuf serta pemikir Islam. Setelah serangkaian observasi dan wawancara mendalam yang dilakukan, penulis berusaha menginterpretasi fenomena yang tertangkap dengan menggunakan rumusan konstruksi sosial dari teori Ibn Al-Farabi. Berdasarkan temuan empiris, didapatkan hasil bahwa masyarakat pemukim Magersari memiliki pemikiran yang positif, optimis dan terbuka. Antar sesama pemukim senantiasa saling membantu dan memiliki rasa kekeluargaan tapi tetap memberi batasan agar tidak terlalu berlebihan. Masyarakat pemukim masih berpegang pada nilai-nilai Islam dan kebudayaan. Namun nilai-nilai ini mulai luntur pada kalangan muda sejalan dengan keengganan mereka untuk berpartisipasi dalam agenda-agenda rutin di dalam permukiman Magersari, maupun agenda-agenda adat-budaya yang diadakan oleh Keraton.